ETNOMATEMATIKA PADA PERMAINAN TRADISIONAL EKLEK SEBAGAI MEDIA PEMBELAJARAN GEOMETRI DI SEKOLAH DASAR - Renni Juwita Tanjung; Suparni Suparni (JURNAL MathEdu (Mathematic Education Journal), 2026)
Ethnomathematics is an approach that connects mathematics with the culture of society. Traditional games, as part of local culture, contain various mathematical activities that can be utilized in learning. This study aims to examine the ethnomathematical elements in the traditional game eklek and to analyze its potential as a learning medium for geometry in elementary schools. The research method used is a descriptive qualitative approach with an ethnographic perspective through observation, documentation, and analysis of the structure of the playing field. The results show that the eklek game contains plane figure concepts such as squares, rectangles, trapezoids, and semicircles, as well as concepts of measurement, number patterns, symmetry, and spatial reasoning. The use of the eklek game in mathematics learning can increase student engagement, conceptual understanding, and positive attitudes toward mathematics